The social brain meets the reactive genome: neuroscience, epigenetics and the new social biology - Meloni, Maurizio (Frontiers in Human Neuroscience, 2014)
The rise of molecular epigenetics over the last few years promises to bring the discourse about the sociality and susceptibility to environmental influences of the brain to an entirely new level. Epigenetics deals with molecular mechanisms such as gene expression, which may embed in the organism “memories” of social experiences and environmental exposures. These changes in gene expression may be transmitted across generations without changes in the DNA sequence. Epigenetics is the most advanced example of the new postgenomic and context-dependent view of the gene that is making its way into contemporary biology. In my article I will use the current emergence of epigenetics and its link with neuroscience research as an example of the new, and in a way unprecedented, sociality of contemporary biology. After a review of the most important developments of epigenetic research, and some of its links with neuroscience, in the second part I reflect on the novel challenges that epigenetics presents for the social sciences for a re-conceptualization of the link between the biological and the social in a postgenomic age. Although epigenetics remains a contested, hyped, and often uncritical terrain, I claim that especially when conceptualized in broader non-genecentric frameworks, it has a genuine potential to reformulate the ossified biology/society debate.